Perspectives on the Correlates of Positive and Negative Spillover between Work and Family: a Study of Selected Banks in Port Harcourt, Rivers State Nigeria - Nkpah, Young A.; Nduonofit, Larry-Love Effiong; Bieh, Nwoke Nwoke (JPAIR Multidisciplinary Research, 2012)
The work-family interface is a systematically defined and measured attempt to evaluate a medium through which promotion of work-family synergistic relationship can thrive. It centres on providing a unique methodology into the work micro-system, family micro-system and individual characteristics. To actualize this, OLS regression analysis was used on data elicited from five (5) commercial banks in Port Harcourt. The study revealed that personality factor alone does not account for the propensities of individuals to experience or report work and family conflict. However, the study recommends that provision of public insurance guaranteeing paid leave for families is necessary for unification of positive or negative spillover effect between work and family.